High Detection Rates for Prostate-specific Membrane Antigen–avid Prostate Cancer Recurrence at Low Prostate-specific Antigen levels on Extended Axial Field-of-view Positron Emission Tomography/Computed Tomography - Sarah Thomas; Jason Callahan; Paul Conway; Daniel Moon; Hugh Morgan; Johanna Ingbritsen; Melissa Munro; Robert E. Ware; Phil Dundee; Rodney J. Hicks (European Urology Open Science)
Background and objective: Although prostate-specific membrane antigen (PSMA) positron emission tomography/computed tomography (PET/CT) has impacted the investigation and management of biochemical recurrence (BCR) of prostate cancer, negative scans are common at low rising prostate-specific antigen (PSA) levels. PET/CT devices with an extended axial field-of-view, such as the Siemens Biograph Vision Quadra (Quadra) scanner, have substantially higher sensitivity than conventional field-of-view scanners. Our aim was to assess whether the enhanced signal-to-noise ratios achieved on the Quadra scanner improve detection of low-volume disease and thereby increase detection of PC at low PSA levels. Methods: We analysed data for the first 300 consecutive patients who underwent clinically indicated PSMA PET/CT for BCR using a Quadra scanner. We assessed scan positivity and the location of detected disease by PSA category. Key findings and limitations: The positivity rate increased with the PSA level from 67% for PSA <0.2 ng/ml to >90% for PSA >1.0 ng/ml (p < 0.05). Disease location also differed by PSA category, with prostate bed recurrence alone identified in 63% of positive cases with PSA <0.2 ng/ml, but <25% of cases with PSA >1.0 ng/ml, and distant metastases present in only 6% of positive cases with PSA <0.2 ng/ml versus >40% of cases with PSA >1.0 ng/ml. In the group with PSA <0.2 ng/ml, pelvic nodal disease without local recurrence was identified in 31% of cases. Conclusions and clinical implications: In comparison to literature data, the Quadra scanner has substantially higher positivity rates at very low PSA levels. At these levels, disease was largely confined to the pelvis and potentially amenable to salvage radiotherapy. However, more than one-third of these patients had disease exclusively outside the prostate bed, with implications for the efficacy and morbidity of current salvage radiotherapy approaches. Patient summary: We investigated a new PET/CT scanner (positron emission tomography/computed tomography) for detection of prostate cancer recurrence. This more sensitive scanner had a higher detection rate, particularly for patients with low PSA (prostate-specific antigen) in their blood. Our results suggest that the new scanner can detect disease recurrence earlier and more accurately than standard PET/CT scanners, which can help in planning further treatment.